Lead‐Free Polycrystalline Ferroelectric Nanowires with Enhanced Curie Temperature. (1st June 2017) - Datta, Anuja; Sanchez‐Jimenez, Pedro E.; Al Orabi, Rabih Al Rahal; Calahorra, Yonatan; Ou, Canlin; Sahonta, Suman‐Lata; Fornari, Marco; Kar‐Narayan, Sohini
Abstract : Ferroelectrics are important technological materials with wide‐ranging applications in electronics, communication, health, and energy. While lead‐based ferroelectrics have remained the predominant mainstay of industry for decades, environmentally friendly lead‐free alternatives are limited due to relatively low Curie temperatures ( T C ) and/or high cost in many cases. Efforts have been made to enhance T C through strain engineering, often involving energy‐intensive and expensive fabrication of thin epitaxial films on lattice‐mismatched substrates. Here, a relatively simple and scalable sol–gel synthesis route to fabricate polycrystalline (Ba0.85 Ca0.15 )(Zr0.1 Ti0.9 )O3 nanowires within porous templates is presented, with an observed enhancement of T C up to ≈300 °C as compared to ≈90 °C in the bulk. By combining experiments and theoretical calculations, this effect is attributed to the volume reduction in the template‐grown nanowires that modifies the balance between different structural instabilities. The results offer a cost‐effective solution‐based approach for strain‐tuning in a promising lead‐free ferroelectric system, thus widening their current applicability. Abstract : Nanowires of (Ba0.85 Ca0.15 )(Zr0.1 Ti0.9 )O3 (BCT‐0.5BZT) are grown using a template‐aided sol–gel synthesis route. These are found to have enhanced ferroelectric Curie temperature ( T C ) of ≈300 °C as compared to ≈90 °C in the bulk. BCT‐0.5BZT in the bulk has limited applicability due to its room‐temperature T C . The studies thus offer a cost‐effective solution, by achieving enhanced T C via strain‐tuning in BCT‐0.5BZT nanowires.